Herbal-Based Community Training For Hypertension Prevention Using TENSITEA - Vina Juliana Anggraeni; Asep Roni; Siti Saidah Mutmainah; Anne Yuliantini; Deden Indra Dinata (Karya Kesehatan Siwalima, 2025)
Hypertension remains one of the most prevalent non-communicable diseases worldwide and is increasingly becoming a health burden in Indonesian communities. Limited knowledge about hypertension and the lack of access to preventive strategies contribute to its high incidence in rural areas. This community empowerment program was conducted to improve public understanding of hypertension and to provide practical training on the production of a herbal tea formulation, known as Tensi Tea, using locally available ingredients such as breadfruit leaves, bay leaves, and cinnamon. The activity took place in Mandalawangi Village and involved community members, local health cadres, and students. The program was implemented in several stages, including educational sessions on hypertension prevention, interactive discussions, and hands-on training in harvesting, processing, and packaging herbal ingredients into tea bags. Participants were actively engaged, demonstrated high enthusiasm, and were able to produce the herbal tea product independently by the end of the training. The results showed an increase in community knowledge regarding risk factors and prevention of hypertension, as well as enhanced skills in producing a simple herbal preparation that has the potential to support both health promotion and local economic opportunities. In conclusion, education on hypertension prevention, accompanied by training on herbal tea, is an effective strategy to empower communities. It is recommended that similar programs be expanded to other rural areas and supported by local health services to ensure sustainability.